Penapisan Cendawan Trichoderma spp. untuk Pengendalian Phytophthora infestans secara in vitro - Susiana Purwantisari; Achmadi Priyatmojo; Retno Peni Sancayaningsih; Rina Sri Kasiamdari (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Late blight disease on potato caused by a plant pathogenic fungus (Phytophthora infestans) is the most important disease in Indonesia. The use of antagonist fungi Trichoderma is an environmentally friendly technology to control the potato disease. The purpose of this study was to determine the ability of Trichoderma spp. to control P. infestans in vitro. Trichoderma spp. have been isolated from suppressive soil at central potato areas in district of Lembang, Bandung, West Java Province. To determine the inhibition ability of Trichoderma spp against P. infestans, a dual culture method was performed. Variable observed was inhibition zone of Trichoderma spp. against P. infestans. The results showed that 9 isolates of Trichoderma were successfuly isolated from suppressive soil, i.e. T. viride (2 isolates), T. atroviride (1 isolate), T. harzianum (1 isolate) and T. aureoviride (5 isolates). All the Trichoderma isolates revealed growth inhibition abality against P. infestans and. The highest growth inhibition (68.6%) was observed by T. viride isolate ( Ti 9).